Fair Pension Policies with Occupation-Specific Aging - Volker Grossmann; Johannes Schünemann; Holger Strulik (Center for Economic Studies and ifo Institute (CESifo), 2021)
We discuss public pension systems in a multi-period overlapping generations model with gerontologically founded human aging and a special focus on occupation-specific morbidity and mortality. We examine how distinct replacement rates for white-collar and blue-collar workers and early retirement policies could be designed to provide a fair and aggregate welfare-enhancing public pension system. Calibrating the model to Germany, we find that a pension system that equalizes relative pension contributions and the relative present-discounted value of expected benefits across occupational groups calls for a significant increase in replacement rates of blue-collar workers. If the statutory retirement age is sufficiently high or the life expectancy gap across occupations is sufficiently large, fair pensions raise aggregate welfare and should feature early retirement incentives.
Keywords: H55; I14; I24; 330; fair pensions; early retirement; occupation; health gradient; life expectancy; replacement rate